2008
DOI: 10.1038/modpathol.3800970
|View full text |Cite
|
Sign up to set email alerts
|

Prostanoid receptor EP1 expression in breast cancer

Abstract: Cyclooxygenase enzymes play an important role in carcinogenesis, and increased expression of cyclooxygenase enzymes has been reported in cancers arising at a number of different sites. Most, if not all of these actions are thought to be mediated by prostaglandin E2 (PGE2). The actions of PGE2 are mediated via four main prostanoid receptors, designated EP1, EP2, EP3 and EP4, based on their different pharmacological properties and secondary messenger pathways. Recently, expression of EP1 has been reported in rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…By RT-PCR and western blotting we first showed that all three cell lines express EP1 as well as EP2-EP4 (Figure 1a, b). Others have reported that EP1 is expressed in the nucleus of malignant cells (13,19). By confocal microscopy, EP1 protein was detected in both the cytoplasm and nucleus of murine mammary tumor cells (Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By RT-PCR and western blotting we first showed that all three cell lines express EP1 as well as EP2-EP4 (Figure 1a, b). Others have reported that EP1 is expressed in the nucleus of malignant cells (13,19). By confocal microscopy, EP1 protein was detected in both the cytoplasm and nucleus of murine mammary tumor cells (Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
“…The only reported finding is that EP1 is detected in both the cytoplasm and nucleus of primary human breast tumors by immunohistochemistry and that EP1 expression in the nucleus of malignant cells correlates with good prognostic markers of progesterone expression and lymph node negative status (13). We investigated the relationship between EP1 expression levels and survival in 55 invasive ductal carcinomas from women who had participated in the Breast Cancer Prognostic Study, a prospective study of 1,306 women newly diagnosed with breast cancer from 1975 to 1983 carried out at the Karmanos Cancer Institute, Detroit, MI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Murine mammary tumors arising in COX-2 transgenic mice have increased expression of EP1, EP2 and EP4, but decreased expression of EP3 in comparison to normal mammary gland [37]. EP1 antagonism prevents chemically-induced breast carcinogenesis in a mouse model [38], however, in advanced human breast cancer, EP1 is associated with lack of lymph node involvement indicating a better prognosis [39]. Several groups have shown that EP receptors mediate migration of tumor cells in vitro [15, 40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…10,116,125 The presence of EP1 has also been demonstrated in human breast cancer cells, and EP4 antagonists have been shown to inhibit breast cancer metastasis. 68,119 Moreover, PGE 2 stimulates through the EP4 receptor the transcription of Id-1, a gene involved in breast cancer metastasis. 114 Via these receptors, PGE 2 is able to promote cell proliferation and survival (through different mechanisms, including suppression of apoptosis), promote tumor angiogenesis (through the production of proangiogenic growth factors such as vascular endothelial growth factor [VEGF] and basic fibroblast growth factor [bFGF]), increase cell invasion and metastasis, and suppress the immune response in order for the tumor cells to escape immunosurveillance (Fig.…”
Section: Cyclooxygenases and Cancermentioning
confidence: 99%